A Modifying of Hill Cipher Algorithm with 3 Substitution Caesar Cipher - Mujaddid, Azzam; Sumarsono, Sumarsono (Proceeding International Conference on Science and Engineering, 2017)
The hill cipher algorithm has the uniqueness of using matrix multiplication in the process where the key used is a matrix that has weaknesses in the process of encryption and decryption. In this paper will be modified to the encryption process with caesar cipher substitution. The principle of the hill cipher algorithm using the multiplication of the 2x2 key matrix of keys is enhanced through process modification lies in the combination of initial character determination using the substitution of 3 caesar ciphers. From the results of this modification can be seen that the more the number of characters processed the time required will be longer. The magnitude of the determinant also affects time and size during the poses. A 1 character increment occurs if the initial character of the encryption process is an odd number.